Analysis of the amount of hard tissue loss in the cavities of different groups of teeth - Bulbuk Олена Василівна; Rozhko Микола Михайлович; Bulbuk Олександр Іванович; Paliychuk Іван Васильович (Actual Dentistry, 2020)
Topicality. Defects of the hard tissues of the teeth remain the most common form of lesions of the dental-maxillary system. The magnitude of the destruction of the tooth crown due to caries or other causes is directly proportional to the duration of its action and may have varying degrees of severity. Depending on the size and location of the defect of the tooth crown and treatment methods change. Despite the high interest of scientists and practitioners in this problem, as well as the large number of studies, there are many unresolved issues in the diagnosis and choice of treatment for dental defects. The aim: to study the clinical features of defects in the hard tissues of the teeth, influencing the choice of method of treatment. Materials and methods. We performed an anthropometric study of different sizes and localization of defects in the hard tissues of the teeth on diagnostic models. Results. During the study of diagnostic models by our proposed method, we determined the volume percentage of various dental defects to the volume of the tooth crown for all groups of teeth. Conclusions. Anthropometric studies and calculations for defects of different groups of teeth allowed to estimate the amount of loss of hard tissues of the tooth in the treatment of patients with this pathology. Systematization of the obtained results will help in the development of methods for optimizing the diagnostic process in the treatment of defects of the hard tissues of the teeth.